Tribal wisdom for business ethics - Rosile, Grace Ann (Emerald Group Publishing Limited, 2016)
Long before Columbus, American Indians had trading routes all across the Americas. How did they maintain this extensive network of trading relationships through the centuries? In this ground-breaking book, leading native and non-native scholars present a fascinating view of American Indian tribal values and indigenous cultures. This 'Tribal Wisdom' offers an ethic of business practice that is relationship-based and community-oriented, fostering a harmonious web of life which includes the natural environment. Many of these traditions have shaped daily conduct in business and personal life among Native Americans for centuries and today the wider business world could find use from relating these tribal values to both ethics and sustainability. Indigenous values incorporate a world-view which recognizes that the natural environment is alive and living a life as important as, and also essential to, human well-being. This indigenous sense of "relationship" begins with the relationship between humans and the natural environment, and then extends to the relationships between and among people. For this reason, indigenous American Indian values embody the very essence of sustainability.